2015
DOI: 10.1155/2015/213874
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Weight Loss Pill Overdose: Sibutramine Hidden in Pepper Pill

Abstract: Supposedly herbal weight loss pills are sold online and are widely used in the world. Some of these products are found to contain sibutramine by FDA and their sale is prohibited. We report a case of a female patient who presented to the emergency department after taking slimming pills. 17-year-old female patient presented to the emergency room with palpitations, dizziness, anxiety, and insomnia. She stated that she had taken 3 pills named La Jiao Shou Shen for slimming purposes during the day. Her vital signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…However, the adulteration of herbal medicines products, like slimming formulations, is a common global concern; pharmaceutical adulterants are frequently found in herbal weight loss products [12][13][14][15][16][17][18][19]. The World Health Organization (WHO) has definitions for substandard, spurious, falsely labeled, falsified, and counterfeit medicinal products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the adulteration of herbal medicines products, like slimming formulations, is a common global concern; pharmaceutical adulterants are frequently found in herbal weight loss products [12][13][14][15][16][17][18][19]. The World Health Organization (WHO) has definitions for substandard, spurious, falsely labeled, falsified, and counterfeit medicinal products.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in many countries, including Iran, have identified the most common undeclared active pharmaceutical ingredients as adulterants in weight loss herbal supplements from many pharmacological categories. These classes include amphetamine analogs, as anorexic agents (sibutramine, desmethyl sibutramine, amfepramone, fenproporex, fenfluramine, ephedrine, norephedrine, phendimetrazine), methylxanthines (caffeine), thyroid hormones, rimonabant, laxatives (phenolphthalein, docusate sodium), diuretics (furosemide, bumetanide, spironolactone, and hydrochlorothiazide), antidepressants (fluoxetine, paroxetine, sertraline, protriptyline, and bupropion), synthetic Phosphodiesterase type-5 (PDE5)-inhibitory drugs (sildenafil, vardenafil, and tadalafil), and opioids (methadone, tramadol) [1,[12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there have been many reports of suspected adverse reactions attributed to such products [7, 50, 51]. There should be tougher legislative action against the promoting and marketing of such products.…”
Section: Discussionmentioning
confidence: 99%
“…Although sibutramine was withdrawn from the U.S. and European markets,1 it is still widely prescribed in many countries, such as Brazil, and is available worldwide as an over-the-counter drug 2,3. There are many descriptions of the psychiatric side effects of sibutramine2-4; however, there is scant information about sibutramine misuse as a compensatory behavior in bulimia nervosa (BN) and its potential consequences.…”
mentioning
confidence: 99%